Towards bio-inspiration, development, and manufacturing of a flapping-wing micro air vehicle - Lane, P.; Throneberry, G.; Fernandez, I.; Hassanalian, M.; Vasconcellos, R. [UNESP]; Abdelkefi, A. (MDPI, 2020)
Throughout the last decade, there has been an increased demand for intricate flapping-wing drones with different capabilities than larger drones. The design of flapping-wing drones is focused on endurance and stability, as these are two of the main challenges of these systems. Researchers have recently been turning towards bioinspiration as a way to enhance aerodynamic performance. In this work, the propulsion system of a flapping-wing micro air vehicle is investigated to identify the limitations and drawbacks of specific designs. Each system has a tandem wing configuration inspired by a dragonfly, with wing shapes inspired by a bumblebee. For the design of this flapping-wing, a sizing process is carried out. A number of actuation mechanisms are considered, and two different mechanisms are designed and integrated into a flapping-wing system and compared to one another. The second system is tested using a thrust stand to investigate the impact of wing configurations on aerodynamic force production and the trend of force production from varying flapping frequency. Results present the optimal wing configuration of those tested and that an angle of attack of two degrees yields the greatest force production. A tethered flight test is conducted to examine the stability and aerodynamic capabilities of the drone, and challenges of flapping-wing systems and solutions that can lead to successful flight are presented. Key challenges to the successful design of these systems are weight management, force production, and stability and control.
Keywords: Bioinspiration; Flapping wing system; Manufacturing; Testing